2008
DOI: 10.3348/kjr.2008.9.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between High Resolution Dynamic MR Features and Prognostic Factors in Breast Cancer

Abstract: ObjectiveTo correlate high resolution dynamic MR features with prognostic factors in breast cancer.Materials and MethodsOne hundred and ninety-four women with invasive ductal carcinomas underwent dynamic MR imaging using T1-weighted three-dimensional fast low-angle shot (3D-FLASH) sequence within two weeks prior to surgery. Morphological and kinetic MR features were determined based on the breast imaging and reporting data system (BI-RADS) MR imaging lexicon. Histological specimens were analyzed for tumor size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
5
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 21 publications
9
70
5
3
Order By: Relevance
“…This finding was not confirmed by a recently published study (36); however, strongest initial enhancement was significantly associated with negative ER and PR status in this investigation (36). Regarding morphologic criteria, spiculated margin has been shown to be a significant independent predictor of lower histologic tumor grade, rim enhancement a significant independent predictor of higher tumor grade, of negative ER and PR status as well as of larger histologic tumor size (39). In our study, we found no significant differences between the calculations of the MDI and histologic characteristics of the carcinomas, such as histologic subtypes, tumor grade, or receptor status.…”
Section: Correlation Of Mri Parameters With Histologic Characteristicscontrasting
confidence: 56%
“…This finding was not confirmed by a recently published study (36); however, strongest initial enhancement was significantly associated with negative ER and PR status in this investigation (36). Regarding morphologic criteria, spiculated margin has been shown to be a significant independent predictor of lower histologic tumor grade, rim enhancement a significant independent predictor of higher tumor grade, of negative ER and PR status as well as of larger histologic tumor size (39). In our study, we found no significant differences between the calculations of the MDI and histologic characteristics of the carcinomas, such as histologic subtypes, tumor grade, or receptor status.…”
Section: Correlation Of Mri Parameters With Histologic Characteristicscontrasting
confidence: 56%
“…Kim and colleagues did not find a relation between HER2 status and initial slope, peak enhancement, time to peak enhancement, or washout ratio (76). Lee and colleagues found no relation between initial slope and HER2 status (79), and Youk and colleagues found no relation between early-phase percentage enhancement and HER2 status (92). Again following Figure 4.…”
Section: Mri Features In Relation To Her2 Overexpression In Breast Camentioning
confidence: 94%
“…No DCE-MRI study excluded patients based on receptor expression. Restricting the meta-analysis to three studies with sub-mm in plane resolution and smaller than 2-mm slice thickness (68,69,79) showed that rim enhancement also increased the chance of HER2 overexpression (pOR, 2.92; 95% CI, 1.42-6.02; P < 0.01; 2 studies; Supplementary Figs. S76-S80).…”
Section: Mri Features In Relation To Her2 Overexpression In Breast Camentioning
confidence: 99%
“…2,3 Previous studies have shown that the size of residual tumours and the response of a tumour to neoadjuvant chemotherapy are related to the recurrence-free survival rate. [4][5][6][7][8] It was also exhibited 8,9 that neoadjuvant chemotherapy could lead to a pathological complete response (pCR) in up to 30% of patients with breast cancers, and these patients showed a better survival outcome than patients with residual cancers. This result emphasizes that prediction of chemotherapeutic effects before treatment could be critical for a successful cancer treatment.…”
Section: Resultsmentioning
confidence: 99%